Analysis of road embankment treated by expanded polystyrene (eps) geofoam using finite element method - Chan, Phui Ling (School of Environmental Engineering, University Malaysia Perlis, 2016)
This research investigates the potential of implementing the application of lightweight fill material, Expanded Polystyrene (EPS) Geofoam in the construction of road embankment. Recently, EPS Geofoam is used widely at various countries in geotechnical engineering field due to its special characteristic. Finite element method is used during the result analysis in this research. There are three types of designed model used which including general road embankment, model of road embankment treated by EPS Geofoam and road embankment treated by EPS Geofoam with excavated until peat layer. Next, three different unit weight of EPS Geofoam which is EPS 15, EPS 20 and EPS 30 are used in comparing the factor of safety for slope and settlement of road embankment. By using the EPS Geofoam in constructing road embankment, it can reduce the settlement and also increase the stability of embankment. Based on the result analysis, designed model of road embankment treated by EPS Geofoam until peat layer obtained the best performance which the settlement are only 80 mm and the factor of safety for slope are the highest, which is 3.4.